2010
DOI: 10.1007/s11426-010-4096-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct palladium/copper oxidative cross-coupling of α-methylstyrene with acrylates

Abstract: Fully palladium/copper catalytic oxidative cross-coupling of acrylates with -methylstyrene was performed in a DMSO/AcOH (1:1) mixture at 60 °C in the air. This improves previous procedures which employed stoichiometric amounts of copper and oxygen. Thus various acrylates were effectively coupled to -methylstyrene giving the expected compounds in moderate to good yields (44%-65%) as a mixture of E and Z isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…2 mol% [Au(SIPr)(O 2 CAd)] (with SIPr: 1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene) and Ad: adamantyl), anhydrous toluene or DMAc, 120-165 °C, 16-20 h) the authors reported a new procedure for transformation of aromatic carboxylic acids to ArH in moderate to good yields (46-97%) but it was not applied to the transformation of cinnamic derivatives. 38 In the field of our ongoing research toward greener synthesis of styrene, stilbene and bibenzyle derivatives, 3,4,7,8,[39][40][41][42][43][44][45][46] we are interested in evaluating the synthesis of various functional styrenes from biosourced substrates. To achieve the procedure in agreement with environmental concerns, studies aiming at decarboxylating selectively cinnamic acids under TM-catalysis and optimizing the reaction conditions were realized.…”
Section: Introductionmentioning
confidence: 99%
“…2 mol% [Au(SIPr)(O 2 CAd)] (with SIPr: 1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene) and Ad: adamantyl), anhydrous toluene or DMAc, 120-165 °C, 16-20 h) the authors reported a new procedure for transformation of aromatic carboxylic acids to ArH in moderate to good yields (46-97%) but it was not applied to the transformation of cinnamic derivatives. 38 In the field of our ongoing research toward greener synthesis of styrene, stilbene and bibenzyle derivatives, 3,4,7,8,[39][40][41][42][43][44][45][46] we are interested in evaluating the synthesis of various functional styrenes from biosourced substrates. To achieve the procedure in agreement with environmental concerns, studies aiming at decarboxylating selectively cinnamic acids under TM-catalysis and optimizing the reaction conditions were realized.…”
Section: Introductionmentioning
confidence: 99%